Intimate relationships in cinema, literature and visual culture - Padva, Gilad ; Buchweitz, Nuri (Palgrave Macmillan, 2020)
This edited volume is an inquiry into the representation of intimate relationships in a diverse array of media including cinema, arts, literature, picture books, advertising and popular music. It examines artistic portrayal of intimate relationships as a subversion of the boundaries between the representable and the non-representable, the real and the surreal, the visceral and the ideal, the embodied and the abstracted, the configured and transfigured. The essays focus on artistic mediation of intimacy in diverse relationships, including heterosexual, same-sex, familial, sibling' , political, and sadomasochistic. The collection offers new interdisciplinary and multicultural perspectives on current trends in the study of popular representations of intimacy; representations that affect and formulate people's most personal inspirations, desires, angsts, dreams and nightmares in an increasingly alienated, industrialized world.